(untitled) (Journal of Human Sciences, 2021)
the critical project of Professor Muhammad Al-Khabu in its general aspect first, that is, in the sum of his critical productions by identifying the signs that characterize this project, and then through his contribution to renewing the consideration of the textual text through an important book of his which is "looking at the Look at stories, Introductions to inferential Narratives".This research is not satisfied with presenting the book and reviewing the conceptual apparatus of the narrative inferential method proposed by Muhammad al-Khabu, but it also goes beyond it to consider, evaluate, and rectify it in such a way that the “the inferred for it”- the reader of the book of Muhammad Al-Khabu, at the end of the article, becomes “the inferred” with all rights.